(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2023)
The present study is a retrospective analysis of 87 cases of death resulting from alleged medical negligence. The cases constituted 1.5% of the total autopsies in a 5-year period. Data were analyzed with respect to age, sex, clinical history, place and duration of treatment, specialty involved, postmortem findings, and cause of death after autopsy and so on. The most common age group was 21–30 years (22.9%) followed by 13–20 years and infant age group (13.9% each). Number of cases was almost equal in both the sexes and most cases were treated at private hospitals. Treatment errors or substandard treatment were the most common allegations. In all, 31 cases had no history of any major preexisting disease, whereas 15 cases had a clinical history of a major preexisting disease. In all, 15 cases were postsurgical deaths, 12 cases were of maternal deaths and 10 cases were of stillbirths. Obstetric surgery and abdominal surgery (33.3% each) were the leading causes of postsurgical allegation of medical negligence followed by cardiac surgery (28.6%) and orthopedic surgery (4.8%). The trends in medical negligence in India along with the role and significance of autopsy in the outcome of such cases have been discussed here.